Relationship between the ST-Segment Resolution and Microvascular Dysfunction in Patients Who Underwent Primary Percutaneous Coronary Intervention - Byung Gyu Kim; Sung Woo Cho; Jeong-Ha Ha; Hyo Seung Ahn; Hye Young Lee; Gwang Sil Kim; Young Sup Byun; Kun Joo Rhee; Jong Chun Nah; Byung Ok Kim (Cardiology Research and Practice)
Objectives. Incomplete ST-segment elevation resolution (STR) occasionally occurs despite successful revascularization of epicardial coronary artery after primary percutaneous coronary intervention (PPCI). The aim of this study was to evaluate the relationship between the degree of STR and the severity of microvascular dysfunction. Methods. A total of 73 consecutive patients with ST-segment elevation myocardial infarction (STEMI) who underwent successful PPCI were evaluated. Serial 12-lead electrocardiography was performed at baseline and at 90 minutes after PPCI. Microvascular dysfunction was assessed by index of microvascular resistance (IMR) immediately after PPCI. Results. Patients were classified into 2 groups: 50 patients with complete STR (STR ≥50%) and 23 patients with incomplete STR (STR <50%). The incomplete STR group had a higher IMR value and lower left ventricular ejection fraction (LVEF), compared with the complete STR group. The degree of STR was significantly correlated with IMR (r = −0.416, P=0.002) and LVEF (r = 0.300, P=0.011). These correlations were only observed in patients with left anterior descending artery (LAD) infarction but not observed in patients with non-LAD infarction. A cutoff IMR value was 27.3 for predicting incomplete STR after PPCI. Conclusion. Incomplete STR after PPCI in patients with STEMI reflects the presence of microvascular and left ventricular dysfunction, especially in patients with LAD infarction.